Analisis Perubahan Tutupan Lahan Di DAS Limboto, Kabupaten Gorontalo, Provinsi Gorontalo. - Ramadhan, Moh; Nurfaika, Nurfaika; Pratama, M. Iqbal Liayong (Universitas Negeri Gorontalo, 2025)
Land cover changes can have various negative impacts on watershed (DAS) areas, such as river sedimentation, increased flood-prone points, agricultural land erosion, and sediment accumulation in river channels. According to data from the Watershed and Protected Forest Management Agency (BPDAS-HL) Bone Bolango, the Limboto watershed has been classified as a critical land area, covering approximately 39,203 hectares. This study aims to analyze land cover changes in the Limboto watershed in the years 2015, 2019, and 2024. The method used is the Maximum Likelihood Classification (MLC) algorithm to accurately classify types of land cover. The analysis results indicate significant changes in the Limboto watershed’s land cover over the past decade. These changes include both increases and decreases in areas such as forests, rice fields, and open land, primarily driven by land use conversion activities carried out by the local community.